Parental choice without parents: families, education and class in a South African township. Issue 1 (2nd January 2017) - Hunter, Mark
Abstract: From the 1980s and 1990s, governments around the world began to champion 'parental choice' over schooling. Much of the existing scholarship has been based on examples taken from the global North. In such settings, where nuclear families are common, a major theme has been the privileged educational strategies and outcomes of middle-class families. Yet this South African study gives attention to gender and family dynamics in helping to explain and understand the large number of schoolchildren travelling to attend historically better-funded schools. It argues that in a setting where the nuclear family accounts for a minority of households, it is necessary to distinguish between the financing of a child's education and the social organization of schooling, including the caring of the child. It contributes to two literatures. First, to Western-centred educational choice literature that has tended to overemphasise nuclear families; second, to South African literature, which is yet to adequately bring into the same analytical frame the marketisation of education and gendered family dynamics.